Da-Cheng-Qi decoction improves severe acute pancreatitis capillary leakage syndrome by regulating tight junction-associated proteins - Tu, Jiamin; Jiang, Yinping; Tu, Lei; Chen, Yafeng; Pan, Liyun; Fan, Xinjuan; Tian, Jiyun; Li, Jianguo; Wang, Xinji; Fu, Honghao; Xu, Bing; Feng, Dianxu (Frontiers in Pharmacology, 2024)
Background and aims: To investigate mechanisms underlying the effects of Da-Cheng-Qi decoction (DCQD) on severe acute pancreatitis (SAP) capillary leakage syndrome. Methods: In this study, a SAP rat model was established using retrograde perfusion of 5% sodium taurocholate into the biliopancreatic duct. The study included three randomized groups: control, SAP (modeling), and DCQD (via gavage at 2 h pre-modeling and 2 and 4 h post-modeling). HPLC was used to analyzed major components of DCQD. Pathological changes and capillary permeability in the rat pancreatic tissues were examined. mRNA levels of claudin 5, occludin, zonula occludin-1 (ZO-1), and junctional adhesion molecules (JAM-C) were assessed using qRT-PCR. Tight junction-associated protein expression was evaluated using immunofluorescence and Western blot analyses. Human umbilical vein endothelial cells (HUVECs) were used to investigate the mechanism m of DCQD. Results: Serum levels of amylase, TNF–α, IL-1β, IL-2, and IL-6 were higher in the SAP group compared to the DCQD group (p < 0.05). DCQD treatment significantly attenuated rat pancreas damage (p < 0.05) and reduced tissue capillary permeability compared to the SAP group (p < 0.05). Claudin 5, occludin, and ZO-1 expression in the rat tissues was upregulated, but JAM-C was downregulated by DCQD treatment (p < 0.05). HUVEC permeability was improved by DCQD in a dose-time-dependent manner compared to the SAP group (p < 0.05). DCQD also upregulated claudin 5, occludin, and ZO-1 expression in vitro (p < 0.05). Conclusion: DCQD can improve capillary permeability in both in vivo and in vitro models of SAP by upregulating expression of claudin 5, occludin, and ZO-1, but not JAM-C.